A retrospective clinical study on blunt trauma abdomen and its management - Rahman, Shahanur; Das, Partha Pratim (International Surgery Journal, 2018)
Background: Blunt trauma abdomen is a common surgical emergency which may present as an isolated problem or as a part of poly trauma. Road traffic (automobile) accident is the most common cause of blunt trauma abdomen. Methods: After initial resuscitation and achieving hemodynamic stability, all patients were subjected to careful history and clinical examination. Depending on the clinical findings, decision for further investigations as four-quadrant aspiration, X-ray of chest and abdomen erect view and abdominal ultrasound were taken. The decision to operate or non-operative management depended on the outcome of clinical examination and results of diagnostic tests. Results: This is a clinical study of 100 patients who were admitted, treated and followed up in Gauhati Medical College and Hospital, Guwahati, Assam, India from 1st July, 2015 to 30th June, 2016. In this study, the incidence of blunt trauma abdomen was found to be 69.78% out of all abdominal trauma patients. The most common cause was found to be road traffic accidents (67%). The commonest age group was 21 to 30 years comprises about 39% of patients. The average age was 30.82 years. Spleen was the most common organ involved (44%). 53.52% of patient having solid organ injured was managed conservatively. Out of 60 operative cases, 25 (41.7%) cases were operated within 3-6 hours. Conclusions: Patients with blunt trauma abdomen should have early and accurate diagnosis and prompt, proper and prudent management to improve overall prognosis.